Examining Urban Dwellers’ Perception of BuilEnvironmental Issues as Framework to Build Collective Consciousness in Indian Cities (Proceedings of the International Conference on Social Sciences, 2020)
The increase in urban population by 1% every year, especially along the fringes of cities has put pressure on the built and unbuilt environment in India. A study estimates 6,95,000 premature deaths in 2010 due to continued exposure to outdoor particulate matter and ozone pollution in Delhi, increasing pressure on governing bodies to provide ‘green’ solutions to address the poisonous air. The choice of where to live in cities is limited and the homogeneity of the built spaces dissolves practice of innovative options. A discussion on an active participation in knowing the built environment is increasing. Under the UNESCO Agenda 21, an active local participation in knowing the built environment is encouraged. A lack of awareness infiltrates the realms of the urban society who have very less ‘say’ to the decision making of these built spaces. What ensues is the repetition of an unsustainable design language. However, their choices are in turn influenced by design choices made by the urban dwelling public in cities. The paper explores which aspects of the built environment is understood by an urban dweller by means of a public survey. The gap in perception of built environment issues based on literature is identified and a critical need for knowledge dissemination is recognized. Various techniques that would facilitate an effective learning among the public is explored and the recognition of a platform that allows the same is found to be imperative in Indian cities.
Keywords: Built Environment; Awareness; Community knowledge; Environmental governance; accessible; holistic